Kepatuhan Kolektif dalam Ritual Sedekah Bumi: Studi Etnografi di Kabupaten Bojonegoro - Hengki Hendra Pradana; Yaoma Tertibi; Maula Safira Putri Tohari (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This research explores collective compliance in the implementation of the Sedekah Bumi ritual in Bojonegoro Regency through an ethnographic approach. Sedekah Bumi is a tradition that involves various elements of society in a ceremony expressing gratitude for crops and prayers for future prosperity. This study aims to understand the social dynamics, symbolic meanings, and the role of collective compliance in the ceremony. Through participatory observation and in-depth interviews with various informants, the study found that collective compliance in Sedekah Bumi is influenced by multiple factors, including the roles of traditional leaders, religious values, and the impact of modernization. The ritual not only strengthens social cohesion and cultural identity but also serves as a crucial means of preserving tradition amidst dynamic social change. In this research, domain analysis techniques were used. The subjects sampled in the study were characterized as natives of Pancur village, regular participants in the Sedekah Bumi events, and of either gender. The subjects included Priyono, a 48-year-old village official; Bani, the 76-year-old caretaker of the village's pepunden; and Farid Amiruddin, a 27-year-old village youth. The study identified four main factors influencing collective compliance: Indoctrination, Habituation, Utility, and Group Identification. The findings concluded that several factors influence the compliance of Pancur Village's residents with the Sedekah Bumi tradition. Indoctrination is introduced since childhood by the surrounding environment, Habituation becomes a habit maintained despite changing times, Utility is celebrated according to individual beliefs to maintain harmony, and Group Identification is preserved as a tribute to ancestral heritage.